Prevalence of parodontopathogenic microflora in patients with valvular pathology of the cardiovascular system - I. P. Mazur; R. M. Vitovsky; M. V. Slobodyanyk; I. V. Martyshchenko (Ukrainian Journal of Cardiovascular Surgery, 2018)
Parodontopathogenic bacteria were found in patients with various cardiovascular diseases, including atherosclerosis, atherosclerotic aneurysms, diseases of peripheral arteries, coronary heart disease, valvular endocarditis. This is due to the presence of periodontal pathogens in the bloodstream.The purpose of this study is to determine the prevalence of periodontal pathogenic microflora in the periodontal pockets (PC) and on the heart valves in patients with acquired heart defects requiring surgical treatment (prosthetic heart valve). Based on the construction of correlation pleiades, determine the features of the relationship between the periodontal pathogenic microflora.Material and research methods. For clinical and microbiological studies, 32 patients with acquired heart defects (mean age 52.4±11.1 years) were examined who underwent surgical treatment at the National Institute of Cardiovascular Surgery them N. M. Amosov. Dental, periodontal, X-ray and microbiological examinations were performed. A microbiological study of the main periodontopathogens (PCR-diagnosis) was performed in the contents of the periodontal pockets (32 samples) and the biological material – the mitral, aortic valve of the heart (32 samples) removed during surgical treatment.The results of the study. Using a microbiological study (PCR-real-time reaction), all of the periodontal pathogenic microflora were found on the remote heart valve (biological material). The highest prevalence in both biological material (60%) and in the periodontal pocket (86.7%) was registered for the periodontopathogenic bacterium Porphyromonas gingivalis. A lower prevalence in biological material was found in T. denticola (40.0%); T. Forsythia (36.7%); P. Intermedia (10.0%) and Aggregatibacter actinomycetemcomitan (10%). Using the method of full correlation analysis with the inclusion of linear and nonlinear correlation and correlation relational algorithms, the following relationships between the periodontal pathogenic microflora are obtained: P. gingivalis – P. Intermedia (ρ=0.47, p=0.006); P. gingivalis – T. forsythensis (ρ=0.72, p=0.001), P. gingivalis – T. denticola (ρ=0.47, p=0.01), P. intermedia – T. denticola (ρ=0.38, p=0.03), T. forsythensis – T. denticola (ρ=0.76, p=0.001). The periodontopathogenic microorganism Aggregatibacter actinomycetemcomitan (Aa) does not correlate with other representatives of the periodontal pathogenic microflora (p=0.3).Findings. A significant prevalence of periodontal tissue diseases (100%) in patients with acquired heart disease, due to transient bacteremia, led to the spread of representatives of the periodontal pathogenic microflora at the remote heart valves. Detection of periodontal pathogenic microflora on the aortic and mitral valves of the heart can adversely affect the course of heart disease.